Molecular characterization of a clinical Haemophilus parainfluenzae isolate with cefotaxime resistance and decreased susceptibility to fluoroquinolones - Faccone, Diego Francisco (2016)
We report an H. parainfluenzae clinical isolate resistant to cefotaxime and with decreased susceptibility to ciprofloxacinrecovered from a patient with cystic fibrosis. The isolate had elevated MICs of ampicillin (256 mg/L), amoxicillin-clavulanate(8 mg/L), cefuroxime (8 mg/L) and cefotaxime (4 mg/L), and showed a β-lactamase-producing amoxicillin-clavulanicacid-resistant (BLPACR) phenotype. A blaTEM-1 plus five amino acid substitutions in the PBP3 were found:Ser385Thr, Val511Ala, Ile519Val, Asn526Lys and Asp551Leu. MIC of ciprofloxacin was 0.5 mg/L, and substitutions ingyrA (Ser84Tyr) and parC (Ser84Phe) genes were detected.